Co9S8–Ni3S2 heterointerfaced nanotubes on Ni foam as highly efficient and flexible bifunctional electrodes for water splitting. (10th March 2019) - Li, Jingwei; Xu, Peiman; Zhou, Rongfu; Li, Ruchun; Qiu, Lijun; Jiang, San Ping; Yuan, Dingsheng
Abstract: Large-scale commercialization of water splitting is still challenging due to the lack of efficient, cost-effective and robust electrodes. In this work, Co9 S8 –Ni3 S2 heterointerfaced nanotubes on Ni foam (Co9 S8 –Ni3 S2 HNTs/Ni) have been successfully developed via a two-step hydrothermal method as a highly efficient, robust and flexible bifunctional electrodes for water splitting. Co9 S8 –Ni3 S2 HNTs are composed of inner 1D Co9 S8 nanotubes surrounded by outer 2D Ni3 S2 nanosheets. Co9 S8 –Ni3 S2 HNTs/Ni electrode achieves 10 mA cm −2 at overpotentials of 85 mV for H2 evolution reaction (HER) and 50 mA cm −2 at overpotential of 281 mV for O2 evolution reaction (OER) in 1 M KOH solution, substantially better than that on single-phased Co9 S8 nanotubes and Ni3 S2 nanosheets on Ni foam. The reason is most likely due to formation of defect-rich heterointerfaces between Co9 S8 nanotubes and Ni3 S2 nanosheets, and the significant change of binding energies of Co 2p and Ni 2p level between the Co9 S8 and Ni3 S2, leading to the synergistic effect on the enhanced catalytic activity for HER and OER. The robust and flexibility of Co9 S8 –Ni3 S2 HNTs/Ni electrodes are demonstrated in an alkaline electrolyzer, delivering 10 mA cm −2 electrolysis current at a cell voltage of 1.59 V, one of the best bifunctional electrodes for water splitting. Owing to the fact that reaction occurs at the defects-rich heterointerfaces, the Co9 S8 -Ni3 S2 HNTs/Ni electrodes are structurally very stable.